2010
DOI: 10.1111/j.1600-051x.2010.01635.x
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐implant reconstruction using autologous periosteum‐derived cells and guided bone regeneration

Abstract: Although successful outcomes have been promoted by using the combined approach, PCs in conjunction with membranes did not provide additional benefit during peri-implant bone regeneration, when compared with the therapeutic approaches used alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…Notably, no immunological reactions related to the use of allogeneic or human cells were reported in these studies. Most studies reported on the use of bone marrow mesenchymal stem cells (BMSC); three studies used periosteal cells (POC) (Mizuno et al, ; Ribeiro et al, , b), two studies used periodontal ligament stem cells (PDLSC) (Kim et al, ; Park et al, ), two studies used adipose tissue‐derived MSC (Bressan et al, ; Xu et al, ) and one study used endothelial progenitor cells (Machtei et al, ). MSC were used in early (one to six) passages, with (seven studies) or without osteogenic pre‐induction.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, no immunological reactions related to the use of allogeneic or human cells were reported in these studies. Most studies reported on the use of bone marrow mesenchymal stem cells (BMSC); three studies used periosteal cells (POC) (Mizuno et al, ; Ribeiro et al, , b), two studies used periodontal ligament stem cells (PDLSC) (Kim et al, ; Park et al, ), two studies used adipose tissue‐derived MSC (Bressan et al, ; Xu et al, ) and one study used endothelial progenitor cells (Machtei et al, ). MSC were used in early (one to six) passages, with (seven studies) or without osteogenic pre‐induction.…”
Section: Resultsmentioning
confidence: 99%
“…Bone marrow is an usual source of bone cells (14), but harvesting these cells are frequently related to pain and morbidity. Alternatively, periosteum has been reported as a reliable source of osteogenic cells (15,16) allowing bone reconstruction around dental implants (17).…”
Section: Discussionmentioning
confidence: 99%
“…47,[90][91][92][93][94][95][96][97][98][99][100] PDCs have been used to construct TEP with and without the use of scaffolds. Rat femoral shaft defects were successfully healed using TEP constructed from PDCs seeded on a polyglycolic acid scaffold.…”
Section: Bridging the Cell-tissue Level: Tissue Engineered Periosteummentioning
confidence: 99%